Aerodynamic coefficients of irregular non-spherical particles at intermediate Reynolds numbers (2022)
In industrial processes such as those related with paper industry, coal or biomass combustion, particles can take irregular non-spherical shapes. However, in related numerical computations the assumption of spherical particle is customary, mainly because the fluid dynamic forces acting on such irregular particles are unknown to a large extent. This contribution aims to generate new information about the flow resistance coefficients (forces and torques) experienced by non-spherical irregular-shaped particles with three different degrees of sphericity ψ (0.7, 0.8 and 0.89) immersed in a uniform flow at intermediate Reynolds numbers (i.e. Re = 1–200). For this purpose, Particle Resolved Direct Numerical Simulations (PR-DNS) are carried out by means of the Ansys-Fluent code using body fitted meshes where the irregular particle is well resolved. The flow coefficients are computed for a set of different particles belonging to the same sphericity group, considering a large number of orientations, which allows the construction of the corresponding distribution functions. Such distributions depend on Reynolds number and particle sphericity and can be reasonably well approximated by Gaussian distributions, which are determined by a mean value and a standard deviation. The obtained drag, lift and torque coefficients display expectedly a scattering around the mean values with a high sensitivity to the irregularity of the surface and particle intrinsic aspect ratio (φ). Additionally, the distribution of the angle formed between the transverse lift force and the transverse torque in the plane orthogonal to the flow direction is computed. The generated information will be used to further pursue a novel statistical model for the fluid dynamic forces and torques acting on irregular particles in the frame of the Lagrangian approach